Effect of gallic acid and catechin on Lactobacillus hilgardii 5w growth and metabolism of organic compounds - Alberto, Maria Rosa (2001)
The effects of different concentrations of (+)-catechin and gallic acid on the growth and metabolism of Lactobacillus hilgardii in different media were evaluated. These phenolic compounds at concentrations normally present in wine not only stimulated the growth rate but also resulted in greater cell densities during the stationary phase of growth in both media. During the first hours of growth both phenolic compounds activated the rate of glucose and fructose utilization and only catechin increased the malic acid consumption rate. Gallic acid and catechin were consumed from the beginning of L. hilgardii growth. All cited effects Were increased when the cells were precultivated in the presence of phenolic compounds, especially in the FT80 medium. As stimulating agents of L. hilgardii 5w growth, gallic acid and catechin could increase the risk of spoilage lactic acid bacteria in wine.